2018
DOI: 10.3892/ol.2018.7728
|View full text |Cite
|
Sign up to set email alerts
|

miR-96 promotes breast cancer metastasis by suppressing MTSS1

Abstract: Novel, non-invasive biomarkers with high sensitivity and specificity are critical for breast cancer treatment, and prognosis. MicroRNA (miR)-96 has been demonstrated to be highly expressed in several solid malignancies, including breast cancer. However, its expression and function in the metastasis and prognosis of breast cancer have not been fully explored, and its regulation mechanisms remain unclear. In the present study, the serum miR-96 expression in healthy controls, benign and malignant breast cancer ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 40 publications
2
22
0
3
Order By: Relevance
“…In BC, miR-96-5p is a positive regulator of the proliferation and metastasis processes, in which the miR-183-5p expression is increased (22)(23)(24)(25). In our previous study, SYVN1 was revealed to be a tumor suppressor in BC (26).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In BC, miR-96-5p is a positive regulator of the proliferation and metastasis processes, in which the miR-183-5p expression is increased (22)(23)(24)(25). In our previous study, SYVN1 was revealed to be a tumor suppressor in BC (26).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, miR-96-5p expression is significantly elevated in BC tissues and cell lines compared with adjacent normal tissues and non-malignant breast epithelial cells, respectively (22,23). The overexpression of miR-96-5p promotes the proliferation and migration of BC cells, while the inhibition of miR-96-5p leads to a decrease in cell viability and an increase in cell death (24,25). miR-96-5p serves an oncogenic role in BC progression, but the regulatory mechanism requires further elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows that miRNAs are involved in the regulation of human cancers and can be used as the diagnosis and therapeutic targets (20,21). For instance, miR-96 is upregulated in breast cancer and promotes breast cancer metastasis by suppressing MTSS1 (22). It was also reported that miR-96 works as a tumor repressor by inhibiting NPTX2 in renal cell carcinoma (23).…”
Section: Discussionmentioning
confidence: 98%
“…Accumulating evidence shows that miRNAs are involved in the regulation of human cancers and can be used as the diagnosis and therapeutic targets [22,23]. For instance, miR-96 is upregulated in breast cancer and promotes breast cancer metastasis by suppressing MTSS1 [24]. It was also reported that miR-96 works as a tumor repressor by inhibiting NPTX2 in renal cell carcinoma [25].…”
Section: Discussionmentioning
confidence: 99%